Clinical Outcomes by Race and Ethnicity in the Systolic Blood Pressure Intervention Trial (SPRINT): A Randomized Clinical Trial. (23rd August 2017) - Still, Carolyn H; Rodriguez, Carlos J; Wright, Jackson T; Craven, Timothy E; Bress, Adam P; Chertow, Glenn M; Whelton, Paul K; Whittle, Jeffrey C; Freedman, Barry I; Johnson, Karen C; Foy, Capri G; He, Jiang; et al.
Abstract: BACKGROUND: The Systolic Blood Pressure Intervention Trial (SPRINT) showed that targeting a systolic blood pressure (SBP) of ≤ 120 mm Hg (intensive treatment) reduced cardiovascular disease (CVD) events compared to SBP of ≤ 140 mm Hg (standard treatment); however, it is unclear if this effect is similar in all racial/ethnic groups. METHODS: We analyzed SPRINT data within non-Hispanic White (NHW), non-Hispanic Black (NHB), and Hispanic subgroups to address this question. High-risk nondiabetic hypertensive patients ( N = 9, 361; 30% NHB; 11% Hispanic) 50 years and older were randomly assigned to intensive or standard treatment. Primary outcome was a composite of the first occurrence of a myocardial infarction, acute coronary syndrome, stroke, decompensated heart failure, or CVD death. RESULTS: Average postbaseline SBP was similar among NHW, NHB, and Hispanics in both treatment arms. Hazard ratios (HRs) (95% confidence interval) (intensive vs. standard treatment groups) for primary outcome were 0.70 (0.57–0.86), 0.71 (0.51–0.98), 0.62 (0.33–1.15) (interaction P value = 0.85) in NHW, NHB, and Hispanics. CVD mortality HRs were 0.49 (0.29–0.81), 0.77 (0.37–1.57), and 0.17 (0.01–1.08). All-cause mortality HRs were 0.61 (0.47–0.80), 0.92 (0.63–1.35), and 1.58 (0.73–3.62), respectively. A test for differences among racial/ethnic groups in the effect of treatment assignment on all-cause mortality was not significant (Hommel-adjusted P value = 0.062) after adjustment for multiple comparisons. CONCLUSION: Targeting a SBP goal of ≤ 120 mm Hg compared to ≤ 140 mm Hg led to similar SBP control and was associated with similar benefits and risks among all racial ethnic groups, though NHBs required an average of 0.3 more medications. CLINICAL TRIALS REGISTRATION: Trial Number NCT01206062, ClinicalTrials.gov Identifier at https://clinicaltrials.gov/ct2/show/NCT01206062 .